Body mass index, body fat percentage, and visceral fat as mediators in the association between health literacy and hypertension among residents living in rural and suburban areas - Nguyen, Tham T.; Nguyen, Minh H.; Nguyen, Yen H.; Nguyen, Thao T. P.; Giap, Manh H.; Tran, Tung D. X.; Pham, Thu T. M.; Pham, Khue M.; Nguyen, Kien T.; Le, Vinh-Tuyen T.; Su, Chien-Tien; Duong, Tuyen Van (Frontiers in Medicine, 2022)
Background Hypertension is a major cause of death and disability worldwide. Enhancing health literacy (HL) may help to alleviate the risk of hypertension and its burden. However, evidence on the association between HL and hypertension and potential mechanisms remain to be explored. Objectives This study examined the association between HL and hypertension; and explored whether body mass index (BMI), body fat percentage (PBF), and visceral fat (VF) were mediators of this association in people who resided in rural and suburban areas in Vietnam. Methods A cross-sectional survey was conducted from 1st July to 31st December 2019, involving 1655 residents and exploring participants’ sociodemographic characteristics, HL, health-related behaviors, comorbidities, body composition, and blood pressure (BP). People with systolic BP ≥ 140 mmHg or diastolic BP ≥ 90 mmHg or using antihypertensive medication were classified as having hypertension. Multiple logistic regression and mediation analyses were used to explore associations. Results The hypertension prevalence was 41.9% (694/1655). In adjusted models, a higher HL score was associated with a lower hypertension likelihood (OR = 0.96; 95%CI = 0.95 to 0.97; p < 0.001). Factors associated with a higher odd of hypertension were overweight/obese (OR = 1.69; 95%CI = 1.24 to 2.29; p = 0.001), high PBF (OR = 2.35; 95%CI = 1.85 to 2.99; p < 0.001), and high VF (OR = 2.27; 95%CI = 1.63 to 3.16; p < 0.001). Notably, PBF significantly mediated the association between HL and hypertension (indirect effect, OR = 0.99; 95%CI = 0.98 to 0.99; p = 0.009; percent mediated = 8.56%). The mediating roles of BMI and VF were not found. Conclusion The prevalence of hypertension was relatively high. People with better HL were less likely to have hypertension. The association between HL and hypertension was partially explained by PBF. Strategic approaches are required to improve people’s HL and body fat which further help to manage hypertension in rural and suburban areas.